Mitochondrial disorders and neurodegeneration - Taanman, Jan-Willem (Henry Stewart Talks, 2019)
Mitochondrial structure and function, Oxidative phosphorylation, Mitochondrial DNA (mtDNA) structure, replication and maternal inheritance, Diseases caused by mutations in mtDNA and therapy, Diseases caused by mutations in nuclear genes coding for mitochondrial proteins